Composite nanomaterial and preparation method and application thereof, and composite biological nanomaterial and preparation method and application thereof

By introducing porous structures into nHA/CTS composite nanomaterials and controlling the pore size distribution, the problem of slow release speed when loading stem cell exosomes is solved, and the rapid release and efficient therapeutic effect of exosomes are achieved.

CN119455131APending Publication Date: 2025-02-18NANJING NORMAL UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411627237.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing nHA/CTS composite nanomaterials are released slowly when loading stem cell exosomes, resulting in the inability to quickly reach effective concentrations, reducing the therapeutic effect and possibly triggering rejection reactions.

Method used

Compound nanomaterials with porous structures, specifically including chitosan and nanohydroxyapatite, are adopted. By controlling the pore size distribution, they can payload stem cell exosomes and control their release to ensure that the exosomes quickly reach effective concentrations.

Benefits of technology

The rapid release of stem cell exosomes at the site of action is achieved, the treatment efficiency is improved, the incidence of rejection is reduced, and the payload inside the exosome is protected from degradation by the internal environment of the body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455131A_ABST
    Figure CN119455131A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biology, and discloses a composite nanomaterial and a preparation method and application thereof, and a composite biological nanomaterial and a preparation method and application thereof. The composite nano-material contains chitosan and nano-hydroxyapatite, the composite nano-material has a porous structure, and in the unit volume of the nano-material, the number of pores with the pore diameter of 50-100 microns accounts for 15-25%, the number of pores with the pore diameter of 50-100 microns accounts for 10-20%, and the number of pores with the pore diameter of 50-100 microns accounts for The ratio of the number of the pores with the pore diameter of 100-150 microns is 35-50%; the ratio of the number of the pores with the pore diameters of 150-200 microns is 5-18%; and the number of the pores with the pore diameter of more than 200 microns accounts for 10-23%. The composite nano material can control the release of the stem cell exosome while loading the stem cell exosome, so that the exosome quickly reaches an effective concentration, the rejection occurrence rate is reduced, and the treatment effect is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of biotechnology, and in particular to a composite nano material, a preparation method and an application thereof. In addition, a composite bio-nano material, a preparation method and an application thereof are also disclosed. Background Art

[0002] Exosomes have multiple functions such as participating in the regulation of angiogenesis, cell apoptosis, inflammatory response and immune response, and stem cell-derived exosomes can play an important role in the differentiation of osteoclasts and osteoblasts through paracrine pathways, promoting bone repair. Therefore, stem cell-derived exosomes are one of the potential bone repair materials.

[0003] Chitosan (CS) has hydrophilic functional groups on its surface, which facilitates cell adhesion and can be used as a carrier for sustained release of drugs in vivo. It is naturally degradable, non-toxic, harmless, and non-irritating to the human body and tissues, has good biocompatibility, and promotes the adhesion and proliferation of various tissue cells. It is widely used in nerve, muscle, and tooth repair materials.

[0004] Nanohydroxyapatite (n-HA) has good biocompatibility and bioactivity and is widely used in bone tissue repair and replacement technology. However, this material has disadvantages such as excessive brittleness and poor bioabsorbability, which limits the use of n-HA in bone replacement and bone repair at load-bearing sites. In addition, simple n-HA is difficult to shape and has poor landfill properties, and irregular or high-density particles usually cause inflammation. Ideal bone scaffold materials should have good biocompatibility, degradability, a good cell-material interface, and suitable mechanical strength to facilitate cell adhesion, proliferation, growth, differentiation, and the growth of new bone and blood vessels. In order to prepare ideal scaffold materials, it is necessary to improve the bioactivity of biomaterials to meet the higher demand for bone scaffold materials.

[0005] nHA / CTS composite nanomaterials are ideal scaffolds for bone transplantation and can also be used as carriers for drugs, exosomes, etc. However, existing nHA / CTS composite nanomaterials take a long time to reach effective concentrations when loaded with stem cell exosomes, and the release rate is slow, which may cause the exosomes to be lost due to blood flow or metabolism, thereby reducing the treatment effect and inducing rejection reactions. Summary of the invention

[0006] The purpose of the present invention is to overcome the problem in the prior art that the release of nHA / CTS composite nanomaterials cannot be controlled when loaded with stem cell exosomes, and to provide a composite nanomaterial and its preparation method and application. The composite nanomaterial can control the release of stem cell exosomes while loading stem cell exosomes, so that the exosomes can quickly reach an effective concentration, reduce the loss of exosomes, and reduce the incidence of rejection reactions.

[0007] In addition, the present invention also provides a composite bio-nanomaterial and a preparation method and application thereof. The composite bio-nanomaterial can control the release of stem cell exosomes, enable the exosomes to quickly reach an effective concentration, reduce the loss of exosomes, and reduce the incidence of rejection reactions.

[0008] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a composite nanomaterial, which contains chitosan and nano-hydroxyapatite. The composite nanomaterial has a porous structure. In the unit volume of the nanomaterial, the number of pores with a pore size of 50-100 μm accounts for 15-25%; the number of pores with a pore size of 100-150 μm accounts for 35-50%; the number of pores with a pore size of 150-200 μm accounts for 5-18%; the number of pores with a pore size of more than 200 μm accounts for 10-23%.

[0009] Preferably, in a unit volume of nanomaterial, the number of pores with a pore size of 50-100 μm accounts for 20-25%; the number of pores with a pore size of 100-150 μm accounts for 40-50%; the number of pores with a pore size of 150-200 μm accounts for 10-18%; the number of pores with a pore size of more than 200 μm accounts for 15-23%.

[0010] Further preferably, in the composite nanomaterial, the average pore diameter of the pores is 126-160 μm.

[0011] Preferably, in the composite nanomaterial, the weight ratio of chitosan to nano-hydroxyapatite is 1:0.05-2, more preferably 1:0.1-0.2;

[0012] The second aspect of the present invention provides a method for preparing a composite nanomaterial, comprising: mixing nano-hydroxyapatite and chitosan under acidic conditions to obtain a composite nanomaterial; the composite nanomaterial is a porous nanomaterial, and in a unit volume of the nanomaterial, the number of pores with a pore size of 50-100 μm accounts for 15-25%; the number of pores with a pore size of 100-150 μm accounts for 35-50%; the number of pores with a pore size of 150-200 μm accounts for 5-18%; the number of pores with a pore size of 200 μm or more accounts for 10-23%.

[0013] Preferably, the acid providing the acidic condition is at least one selected from acetic acid, lactic acid, citric acid, formic acid and malic acid.

[0014] Further preferably, the acid providing the acidic condition is acetic acid.

[0015] Further preferably, in the acidic condition, the molar concentration of the acid providing the acidic condition is 0.1-0.3 mol / L.

[0016] Further preferably, in the composite nanomaterial, the weight ratio of the chitosan to the nano-hydroxyapatite is 1:0.05-2, preferably 1:0.1-0.2.

[0017] Further preferably, relative to 1 g of the nano-hydroxyapatite, the amount of the acid used is 250-500 mL.

[0018] Further preferably, the mixing process also includes adding a cross-linking agent.

[0019] Further preferably, the mass ratio of the cross-linking agent to the chitosan is 5-6:1.

[0020] Further preferably, the cross-linking agent is a glutaraldehyde solution, and the concentration of glutaraldehyde in the glutaraldehyde solution is 25-50 wt %.

[0021] The third aspect of the present invention provides the use of the composite nanomaterial described in the first aspect or the composite nanomaterial prepared by the preparation method described in the second aspect in loading stem cell exosomes, preferably human umbilical cord blood mesenchymal stem cell exosomes.

[0022] The fourth aspect of the present invention provides a composite biological nanomaterial, comprising a composite nanomaterial and stem cell exosomes loaded on the composite nanomaterial; the composite nanomaterial is the composite nanomaterial described in the first aspect above or the composite nanomaterial obtained by the preparation method described in the second aspect above.

[0023] Preferably, the loading amount of the stem cell exosomes in the unit mass of the composite bio-nanomaterial is 0.1-0.2%.

[0024] The fifth aspect of the present invention provides a method for preparing a composite biological nanomaterial, comprising: mixing stem cell exosomes and a composite nanomaterial in the presence of a solvent; the composite nanomaterial is the composite nanomaterial described in the first aspect above or the composite nanomaterial obtained by the preparation method described in the second aspect above.

[0025] Preferably, the mixing conditions include: temperature of 0-4°C, time of 10-14h, pH of 7.2-7.4;

[0026] Preferably, the concentration of the stem cell exosomes in the solvent is 10-30 μg / mL.

[0027] The sixth aspect of the present invention provides the use of the composite bio-nanomaterial described in the fourth aspect or the composite bio-nanomaterial prepared by the preparation method described in the fifth aspect as a bone tissue engineering biomaterial.

[0028] Through the above technical solution, the beneficial effects of the present invention are:

[0029] The composite nanomaterial containing chitosan and nano-hydroxyapatite provided by the present invention is a porous nanomaterial, and the distribution of the pore size of the composite nanomaterial is controlled within a specific range, so that it can load stem cell exosomes while controlling the release of stem cell exosomes at the site of action, so that the exosomes at the site of action quickly reach an effective concentration, and the high local concentration of exosomes can more effectively interact with target cells and tissues, improve treatment efficiency, reduce the incidence of rejection reactions, and will not make the exosome concentration at the site of action too high. It can also protect the effective load inside the exosomes from being degraded by the body environment.

[0030] Both chitosan and nano-hydroxyapatite have good biocompatibility, which helps to improve the stability of drugs and reduce immunogenicity. At the same time, chitosan and nano-hydroxyapatite materials are easy to process, exist naturally and have relatively low costs, making them economical and feasible in production. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a transmission electron microscopic image of exosomes of human umbilical cord blood mesenchymal stem cells extracted in the preparation example of the present invention;

[0032] Figure 2 This is a cell uptake diagram of human umbilical cord blood mesenchymal stem cell exosomes extracted in the preparation example of the present invention;

[0033] Figure 3 is an optical image of a mixed solution of nano-hydroxyapatite and chitosan in Example 1 of the present invention;

[0034] Figure 4 is an optical image of the composite nanomaterial 1 prepared in Example 1 of the present invention;

[0035] Figure 5 This is a SEM image of the composite nanomaterial 1 loaded with human umbilical cord blood mesenchymal stem cell exosomes prepared in the application example of the present invention;

[0036] Figure 6 is a biocompatibility graph of the composite nanomaterial 1 prepared in Example 1 of the present invention;

[0037] Figure 7It is a comparison chart of the osteogenic activity of the composite nanomaterial experimental group loaded with human umbilical cord blood mesenchymal stem cell exosomes prepared in the application example of the present invention and the negative and positive control groups. DETAILED DESCRIPTION

[0038] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0039] The first aspect of the present invention provides a composite nanomaterial, which contains chitosan and nano-hydroxyapatite, and has a porous structure. In the unit volume of the nanomaterial, the number of pores with a pore size of 50-100 μm accounts for 15-25%, specifically 15%, 20%, 25%, or any value between the above two values; the number of pores with a pore size of 100-150 μm accounts for 35-50%, specifically 35%, 40%, 45%, 50%, or any value between the above two values; the number of pores with a pore size of 150-200 μm accounts for 5-18%, specifically 5%, 10%, 15%, 18%, or any value between the above two values; the number of pores with a pore size of more than 200 μm accounts for 10-23%, specifically 10%, 15%, 20%, 23%, or any value between the above two values.

[0040] Studies have found that simple nano-hydroxyapatite is difficult to shape, has poor landfilling properties, and irregular or high-density particles usually cause inflammation. Chitosan can be used to modify nano-hydroxyapatite to obtain microspheres that can be evenly filled, which helps bone growth and reduces inflammation. It is an ideal carrier for exosome implantation and bone repair. The inventors of the present invention unexpectedly discovered in a study of composite nanomaterials containing chitosan and nano-hydroxyapatite as carriers that the composite nanomaterial is a porous nanomaterial that controls the distribution of the pore size of the composite nanomaterial within a specific range. It can load stem cell exosomes while controlling the release of stem cell exosomes at the site of action, so that the exosomes at the site of action quickly reach an effective concentration, reduce the incidence of rejection reactions, and will not make the exosome concentration at the site of action too high. It can also protect the payload inside the exosomes from being degraded by the in vivo environment.

[0041] According to the present invention, preferably, in a unit volume of nanomaterials, the number of holes with a pore size of 50-100 μm accounts for 20-25%, specifically 20%, 22%, 25%, or any value between the above two values; the number of holes with a pore size of 100-150 μm accounts for 40-50%, specifically 40%, 45%, 50%, or any value between the above two values; the number of holes with a pore size of 150-200 μm accounts for 10-18%, specifically 10%, 14%, 18%, or any value between the above two values; the number of holes with a pore size of 200 μm or more accounts for 15-23%, specifically 15%, 20%, 23%, or any value between the above two values. The inventors found that when the above preferred embodiment is adopted, the release of stem cell exosomes at the site of action can be further controlled when loading stem cell exosomes, so that the exosomes at the site of action quickly reach an effective concentration.

[0042] According to the present invention, further preferably, in the composite nanomaterial, the average pore size of the pores is 126-160 μm, specifically 126 μm, 130 μm, 135 μm, 140 μm, 145 μm, 150 μm, 155 μm, 160 μm, or any value between the above two values. The inventors found that when the above preferred embodiment is adopted, the effect of controlling the release of stem cell exosomes at the site of action is better when loading stem cell exosomes, so that the exosomes at the site of action quickly reach an effective concentration.

[0043] According to the present invention, preferably, in the composite nanomaterial, the weight ratio of chitosan to nano-hydroxyapatite is 1:0.05-2, specifically 1:0.05, 1:0.1, 1:0.5, 1:1, 1:1.5, 1:2, or any ratio between the above two ratios, more preferably 1:0.1-0.2, specifically 1:0.1, 1:0.2, or any ratio between the above two ratios. The inventors found that when the above preferred embodiment is adopted, the release of stem cell exosomes at the site of action can be further controlled when the stem cell exosomes are loaded, so that the exosomes at the site of action quickly reach an effective concentration.

[0044] The second aspect of the present invention provides a method for preparing a composite nanomaterial, comprising: mixing nano-hydroxyapatite and chitosan under acidic conditions to obtain a composite nanomaterial; the composite nanomaterial is a porous nanomaterial, and in a unit volume of the nanomaterial, the number of pores with a pore size of 50-100 μm accounts for 15-25%, specifically 15%, 20%, 25%, or any value between the above two values; the number of pores with a pore size of 100-150 μm accounts for 35-50%, specifically 35%, 40%, 45%, 50%, or any value between the above two values; the number of pores with a pore size of 150-200 μm accounts for 5-18%, specifically 5%, 10%, 15%, 18%, or any value between the above two values; the number of pores with a pore size of more than 200 μm accounts for 10-23%, specifically 10%, 15%, 20%, 23%, or any value between the above two values. The inventors found that the composite nanomaterial prepared by the above method can control the distribution of the pore size of the composite nanomaterial within a specific range, can load stem cell exosomes while controlling the release of stem cell exosomes at the site of action, so that the exosomes at the site of action can quickly reach an effective concentration.

[0045] According to the present invention, preferably, the acid providing the acidic condition is selected from at least one of acetic acid, lactic acid, citric acid, formic acid and malic acid. Further preferably, the acid providing the acidic condition is acetic acid. The inventors found that when the acid providing the acidic condition is acetic acid, the prepared composite nanomaterial has better performance, chitosan and nano-hydroxyapatite are more evenly combined, and the void size of the obtained composite nanomaterial is distributed within a specific range, so that the composite material can control the release of stem cell exosomes at the site of action while loading stem cell exosomes, so that the exosomes at the site of action quickly reach an effective concentration.

[0046] According to the present invention, further preferably, in the acidic condition, the molar concentration of the acid providing the acidic condition is 0.1-0.3 mol / L, specifically 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, or any value between the above two values. The inventors found that when the above preferred embodiment is adopted, chitosan and nano-hydroxyapatite are combined more evenly, and the void size of the obtained composite nanomaterial is distributed within a specific range, so that the composite material can control the release of stem cell exosomes at the site of action while loading stem cell exosomes, so that the exosomes at the site of action quickly reach an effective concentration.

[0047] According to the present invention, further preferably, in the composite nanomaterial, the weight ratio of the chitosan and the nano-hydroxyapatite is 1:0.05-2, specifically 1:0.05, 1:0.1, 1:0.5, 1:1, 1:1.5, 1:2, or any ratio between the above two ratios, more preferably 1:0.1-0.2, specifically 1:0.1, 1:0.2, 1:0.3, or any ratio between the above two ratios. The inventors found that when the above preferred embodiment is adopted, the release of stem cell exosomes at the site of action can be further controlled when the stem cell exosomes are loaded, so that the exosomes at the site of action quickly reach an effective concentration.

[0048] According to the present invention, further preferably, relative to 1g of the nano-hydroxyapatite, the amount of the acid is 250-500mL, specifically 250mL, 300mL, 350mL, 400mL, 450mL, 500mL, or any value between the above two values. The inventors found that when the above preferred embodiment is adopted, chitosan and nano-hydroxyapatite are combined more evenly, and the void size of the obtained composite nanomaterial is distributed within a specific range, so that the composite material can control the release of stem cell exosomes at the site of action while loading stem cell exosomes, so that the exosomes at the site of action quickly reach an effective concentration.

[0049] According to the present invention, preferably, the preparation method also includes post-treatment, and the post-treatment process includes shaping, desolventizing, alkali washing and sterilization. Specifically, shaping is performed by pre-freezing a mold to obtain a skeleton of a composite nano material; desolventizing is performed by freeze-drying the shaped skeleton to obtain a scaffold of a composite nano material; the obtained composite nano material scaffold is placed in an alkaline solution for alkali washing, neutralizing and removing the acidic substances in the material in the scaffold, and then rinsed with water several times to neutrality and freeze-dried and sterilized again to obtain the final composite nano material. The sterilization method can adopt a sterilization method commonly used in the art, such as ultraviolet irradiation. The inventors have found that when the above preferred embodiment is adopted, the composite nano material can be prepared into various models according to actual needs, the scope of application can be expanded, and the release of stem cell exosomes at the site of action can be further controlled when loading stem cell exosomes, so that the exosomes at the site of action can quickly reach an effective concentration.

[0050] According to the present invention, it is further preferred that the alkaline solution of the alkali washing is at least one of a sodium hydroxide solution, a potassium hydroxide solution, a calcium hydroxide solution, an ammonia solution and a sodium carbonate solution. More preferably, the alkaline solution is a sodium hydroxide solution. It is further preferred that the molar concentration of the solute in the alkaline solution is 1-3 mol / L, specifically 1 mol / L, 2 mol / L, 3 mol / L, or any value between the above two values. The inventors found that when the above preferred embodiment is adopted, chitosan and nano-hydroxyapatite are combined more evenly, and the void size of the obtained composite nanomaterial is distributed within a specific range, so that the composite material can control the release of stem cell exosomes at the site of action while loading stem cell exosomes, so that the exosomes at the site of action quickly reach an effective concentration.

[0051] According to the present invention, preferably, the mixing process also includes adding a crosslinking agent. Further preferably, the mass ratio of the crosslinking agent to the chitosan is 5-6:1, specifically 5:1, 6:1, or any value between the above two values; more preferably, the crosslinking agent is a glutaraldehyde solution, and the concentration of glutaraldehyde in the glutaraldehyde solution is 25-50wt%, specifically 25wt%, 35wt%, 45wt%, 50wt%, or any value between the above two values. The inventors found that when the above preferred embodiment is adopted, the binding and uniformity of nano-hydroxyapatite and chitosan can be improved, and the void size of the obtained composite nanomaterial is distributed within a specific range, so that the composite material can control the release of stem cell exosomes at the site of action while loading stem cell exosomes, so that the exosomes at the site of action quickly reach an effective concentration.

[0052] As a relatively preferred embodiment of the present invention, the preparation method of the composite nanomaterial is as follows: weigh 0.08-0.24g of nano-hydroxyapatite, add it to 36-40mL of 0.1-0.3mol / L dilute acetic acid solution, ice bath ultrasonic oscillation for 15-20min to obtain a uniform gray-white suspension, then add 0.8-0.9g of chitosan, the weight ratio of chitosan to nano-hydroxyapatite is 1:0.1-0.3, after magnetic stirring for 2-3h, add 4-5mL of glutaraldehyde solution, the mass ratio of cross-linking agent to chitosan is 5-6:1; continue to stir for 30-40min, pack it into a cylindrical mold with a diameter of 5mm and a length of 1cm for shaping, pre-freeze it at -(20-80)℃ for 24-48h, and then freeze-dry it to obtain a skeleton; immerse the obtained skeleton in 1-3mol / L The nanocomposite is immersed in a NaOH solution for 12-24 hours, and then taken out and rinsed with deionized water for several times until it becomes neutral. After secondary freeze-drying, it is sterilized to obtain a composite nanomaterial.

[0053] The third aspect of the present invention provides the use of the composite nanomaterial described in the first aspect or the composite nanomaterial prepared by the preparation method described in the second aspect in loading stem cell exosomes, preferably human umbilical cord blood mesenchymal stem cell exosomes. The inventors found that when the above-mentioned composite nanomaterial is used to load stem cell exosomes, the void size of the obtained composite nanomaterial is distributed within a specific range, so that the composite material can control the release of stem cell exosomes at the site of action while loading stem cell exosomes, so that the exosomes at the site of action quickly reach an effective concentration.

[0054] The extraction of exosomes from human umbilical cord blood mesenchymal stem cells can be carried out by a method commonly used in the art. Exemplarily, the following method can be used to extract exosomes: The specific process includes the following steps:

[0055] S1. Take P3 generation HUCB-MCSs and culture them in mesenchymal stem cell medium (serum-free). After 2-3 days, collect the sterile supernatant and freeze it at -(20-80)℃;

[0056] S2. Thaw the supernatant frozen at -(20-80)℃ in a 25-30℃ water bath and place the completely thawed supernatant on ice;

[0057] S3, (3000-4000) × g, 30-40 min, to remove cell debris;

[0058] S4. Add ESC reagent to the centrifuged supernatant in proportion, vortex for 1-2 minutes, and place at 0-4°C for 2-4 hours;

[0059] S5, mixed solution (8000-10000) × g, 1-1.5 h, 0-4 ° C, precipitation is visible;

[0060] S6. Discard the supernatant, add (1-1.5)×PBS in proportion, and evenly blow the centrifugal precipitate;

[0061] S7, resuspend (10000-12000) × g, 2-3 min, 0-4 ° C, retain the supernatant;

[0062] S8. Transfer the crude exosomes into the upper chamber of the EPF column, centrifuge at (3000-4000) × g for 10-15 min at a temperature of 0-4°C, and collect the liquid at the bottom of the tube, which is the purified human umbilical cord blood mesenchymal stem cell exosomes (HUCB-MCSs-Exo).

[0063] The fourth aspect of the present invention provides a composite bio-nanomaterial, comprising a composite nanomaterial and stem cell exosomes loaded on the composite nanomaterial; the composite nanomaterial is the composite nanomaterial described in the first aspect or the composite nanomaterial prepared by the preparation method described in the second aspect. Preferably, in the unit mass of the composite bio-nanomaterial, the loading amount of the stem cell exosomes is 0.1-0.2%, specifically 0.1%, 0.2%, or any value between the above two values. The inventors have found that the composite bio-nanomaterial prepared by the above method can control the distribution of the pore size of the composite nanomaterial within a specific range, can load the stem cell exosomes while controlling the release of the stem cell exosomes at the site of action, so that the exosomes at the site of action quickly reach an effective concentration.

[0064] The fifth aspect of the present invention provides a method for preparing a composite bio-nanomaterial, comprising: mixing stem cell exosomes and a composite nanomaterial in the presence of a solvent; the composite nanomaterial is the composite nanomaterial described in the first aspect or the composite nanomaterial prepared by the preparation method described in the second aspect. The inventors have found that the composite bio-nanomaterial prepared by the above method can control the distribution of the pore size of the composite nanomaterial within a specific range, can load stem cell exosomes and control the release of stem cell exosomes at the site of action, so that the exosomes at the site of action quickly reach an effective concentration.

[0065] According to the present invention, preferably, the mixing conditions include: temperature of 0-4°C, specifically 0°C, 1°C, 2°C, 3°C, 4°C, or any value between the above two values; time of 10-14h, specifically 10h, 11h, 12h, 13h, 14h, or any value between the above two values; pH of 7.2-7.4, specifically 7.2, 7.3, 7.4, or any value between the above two values. The inventors found that by adopting the above preferred embodiment, the stem cell exosomes can be better loaded on the composite nanomaterial, and the pore size of the composite nanomaterial can be controlled to be distributed within a specific range, so that the stem cell exosomes can be loaded while controlling the release of the stem cell exosomes at the site of action, so that the exosomes at the site of action can quickly reach an effective concentration.

[0066] According to the present invention, preferably, the concentration of stem cell exosomes in the solvent is 10-30 μg / mL, specifically 10 μg / mL, 20 μg / mL, 30 μg / mL, or any value between the above two values. The inventors found that by adopting the above preferred embodiment, the stem cell exosomes can be better loaded on the composite nanomaterial, and the pore size of the composite nanomaterial can be controlled to be distributed within a specific range, so that the stem cell exosomes can be loaded while controlling the release of the stem cell exosomes at the site of action, so that the exosomes at the site of action can quickly reach an effective concentration.

[0067] As a relatively preferred embodiment of the present invention, the preparation method of the composite bio-nanomaterial loaded with stem cell exosomes is as follows: immerse the shaped composite nanomaterial scaffold in a PBS solution of stem cell exosomes, the concentration of the stem cell exosomes is 10-30 μg / mL, immerse for 10-14 hours at 0-4°C and pH 7.2-7.4, take out, pre-freeze at -(20-40)°C for 24-48 hours, and then freeze-dry to obtain a composite bio-nanomaterial loaded with stem cell exosomes.

[0068] The sixth aspect of the present invention provides the use of the composite bio-nanomaterial described in the fourth aspect or the composite bio-nanomaterial prepared by the preparation method described in the fifth aspect as a bone tissue engineering biomaterial. The inventors have found that when stem cell exosomes are loaded on the composite nanomaterial as a bone tissue engineering biomaterial, and more preferably a bone repair material, the pore size of the composite nanomaterial can be controlled to be distributed within a specific range, so that the stem cell exosomes can be loaded while controlling the release of the stem cell exosomes at the site of action where bone repair is required, so that the exosomes at the site of action quickly reach an effective concentration, improve the effect of bone repair, and reduce the incidence of rejection.

[0069] Compared with simple CS / nHA composite nanomaterials, CS / nHA composite nanomaterials loaded with human umbilical cord blood mesenchymal stem cell exosomes (HUCB-MCSs-Exo) can enhance the osteogenic ability of cells and promote cell proliferation. This artificial bone complex provides a new idea and direction for tissue engineering to repair large-area bone defects.

[0070] The present invention will be described in detail below through examples.

[0071] In the following examples, human umbilical cord blood mesenchymal stem cells were purchased from Cebio Biotech (China), and the relevant experiments conducted have been approved by the Ethics Committee, and the Ethics Committee approval number is 2023L-10-09. The colorimetric quantitative detection kit for osteogenic differentiation potential of stem cells was purchased from Shanghai Yuduo Biotechnology Co., Ltd.; PBS was purchased from Hyclone (USA); BCA protein quantification kit and MTT kit were both purchased from Biyuntian Biotechnology (China); mesenchymal stem cell culture medium was purchased from TAKARA (Japan); cell supernatant exosome extraction kit was purchased from Beijing Solebow Technology Co., Ltd. For those examples and comparative examples where specific conditions are not specified, they are all carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.

[0072] Preparation Example

[0073] Extraction of exosomes from human umbilical cord blood mesenchymal stem cells (HUCB-MCSs)

[0074] The specific process includes the following steps:

[0075] S1. Take P3 generation HUCB-MCSs and culture them in mesenchymal stem cell medium (serum-free). After 2 days, collect the sterile supernatant and freeze it at -80°C.

[0076] S2. Thaw the supernatant frozen at -80°C in a 25°C water bath and place the completely thawed supernatant on ice;

[0077] S3, 3000 × g, 30 min, to remove cell debris;

[0078] S4. Add ESC reagent to the centrifuged supernatant in proportion, vortex for 1 min, and place at 4°C for at least 2 h.

[0079] S5, mixed solution 10000 × g, 1 h, 4 ° C, precipitate can be seen;

[0080] S6. Discard the supernatant, add 1× PBS in proportion, and evenly blow the centrifugal precipitate;

[0081] S7, resuspend at 12000 × g, 2 min, 4 °C, retain the supernatant;

[0082] S8. Transfer the crude exosomes into the upper chamber of the EPF column, centrifuge at 3000×g for 10 min at 4°C, and collect the liquid at the bottom of the tube, which is the purified human umbilical cord blood mesenchymal stem cell exosomes (HUCB-MCSs-Exo).

[0083] 10 μL of separated and purified exosome solution was added dropwise to the copper mesh. After standing, it was negatively stained with 3% phosphotungstic acid for 5 minutes, dried in the air, and observed and photographed under a transmission electron microscope (80KV, 150000×). After culturing BMSCs (bone marrow mesenchymal stem cells) for 24 hours, the culture medium was replaced with fresh medium, and PE-CD9-labeled exosomes were added. The culture medium was discarded after sampling at 0.5 hours and 3 hours, and Honchst33342 was incubated in the dark for 10 minutes. The fluorescence was detected by laser confocal microscopy and photographed. The morphology of HUCB-MCSs-Exo can be observed under a transmission electron microscope, and the diameter is about 120nm (such as Figure 1 Cell uptake experiments showed that HUCB-MCSs-Exo could be taken up by BMSCs (as shown in Figure 2 At the same time, HUCB-MCSs-Exo can be marked by CD9, confirming that the one extracted by the kit is HUCB-MCSs-Exo.

[0084] Example 1

[0085] Preparation of composite nanomaterials 1

[0086] Weigh 0.08g of nano-hydroxyapatite, add to 36mL of 0.1mol / L acetic acid solution, and ultrasonically vibrate in an ice bath for 15min to obtain a uniform gray-white suspension, then add 0.8g of chitosan, the weight ratio of chitosan to nano-hydroxyapatite is 1:0.1, and after magnetic stirring for 2h, add 4mL of 25wt% glutaraldehyde solution, the mass ratio of cross-linking agent to chitosan is 5:1; continue stirring for 30min, and then pack into a cylindrical mold with a diameter of 5mm and a length of 1cm for shaping, pre-freeze at -20℃ for 24h, and then freeze-dry to obtain a skeleton; immerse the obtained skeleton in 1mol / L NaOH solution for 12h, take it out and rinse it with deionized water several times until it is neutral, freeze-dry it twice, and sterilize it to obtain composite nanomaterial 1. The optical image of the mixed solution of nano-hydroxyapatite and chitosan is as follows: Figure 3 As shown; the optical image of the prepared composite nanomaterial 1 is as shown Figure 4 shown.

[0087] Example 2

[0088] Composite nanomaterial 2 was prepared according to the method of Example 1, except that

[0089] Replace 0.08g of nanohydroxyapatite with 0.16g of nanohydroxyapatite, and the weight ratio of chitosan to nanohydroxyapatite is 1:0.2;

[0090] Replace the 12h immersion in 1mol / L NaOH solution with 24h immersion in 3mol / L KOH solution;

[0091] The addition of 4 mL of 25 wt % glutaraldehyde solution was replaced by the addition of 4.2 mL of 25 wt % glutaraldehyde solution, and the mass ratio of the cross-linking agent to chitosan was 6:1.

[0092] Example 3

[0093] The composite nanomaterial 3 was prepared according to the method of Example 1, except that:

[0094] Replace 0.08g of nano-hydroxyapatite with 0.24g of nano-hydroxyapatite, and the weight ratio of chitosan to nano-hydroxyapatite is 1:0.3;

[0095] The immersion in 1 mol / L NaOH solution for 12 h was replaced by immersion in 2 mol / L calcium hydroxide solution for 14 h;

[0096] The addition of 4 mL of 25 wt % glutaraldehyde solution was replaced by the addition of 6 mL of 30 wt % glutaraldehyde solution.

[0097] Example 4

[0098] The composite nanomaterial 4 was prepared according to the method of Example 1, except that 36 mL of 0.1 mol / L acetic acid solution was replaced with 36 mL of 0.1 mol / L formic acid solution.

[0099] Example 5

[0100] The composite nanomaterial 5 was prepared according to the method of Example 1, except that 36 mL of 0.1 mol / L acetic acid solution was replaced with 36 mL of 0.1 mol / L lactic acid solution.

[0101] Example 6

[0102] The composite nanomaterial 6 was prepared according to the method of Example 1, except that 36 mL of 0.1 mol / L acetic acid solution was replaced with 72 mL of 0.1 mol / L formic acid solution.

[0103] Comparative Example 1

[0104] Preparation of n-HA: Accurately weigh 14.76g Ca(OH)2 and 11.71g concentrated H3PO4, and dissolve Ca(OH)2 in ethanol to prepare a 5wt% suspension, referred to as A liquid; dilute the concentrated H3PO4 to a 10wt% aqueous solution, referred to as B liquid. Slowly drip B liquid into A liquid under stirring at room temperature, with a dripping speed of 4mL / min, and the pH value is maintained at about 10 during the process. After the addition is completed, continue stirring for 24 hours. The resulting slurry is aged at room temperature for one day, and the precipitate is filtered, washed, vacuum dried at 80℃, and ground into powder.

[0105] Preparation of n-HA / CS composite material: According to the stoichiometric ratio of HA Ca / P = 1.67, appropriate amounts of Ca(OH)2 and H3PO4 were weighed, and Ca(OH)2 was dissolved in ethanol to prepare a 5wt% suspension, referred to as A liquid; concentrated phosphoric acid was diluted to a 10wt% aqueous solution; then CS powder was weighed and dissolved in a 2wt% acetic acid aqueous solution, stirred continuously for 5 hours, and filtered to obtain a completely transparent 3wt% CS solution. The prepared phosphoric acid solution was poured into the CS solution and stirred thoroughly to obtain B liquid. The entire reaction was carried out at room temperature, and B liquid was slowly dripped into A liquid under stirring conditions, with a dripping speed of 4mL / min, and the pH value of the process was maintained at about 10. After the addition was completed, stirring was continued for 24 hours. The resulting slurry was aged at room temperature for one day, the precipitate was filtered, washed, and dispensed into a cylindrical mold with a diameter of 5mm and a length of 1cm for finalization, and vacuum dried at 80°C to prepare a nanocomposite material 7.

[0106] The nanocomposites prepared in the above examples and comparative examples were randomly photographed at different regions using a scanning electron microscope, and the pore size and distribution in the pictures were statistically analyzed to obtain the average value. The pore size distribution in the above examples 1-6 and comparative example 1 is shown in Table 1.

[0107] Table 1

[0108]

[0109]

[0110] Application Examples

[0111] Preparation of composite bionanomaterials loaded with stem cell exosomes

[0112] The cylindrical composite nanomaterial scaffolds 1-7 with a diameter of 5 mm and a length of 1 cm prepared in Examples 1 to 6 and Comparative Example 1 were respectively immersed in a PBS solution of stem cell exosomes with a concentration of stem cell exosomes of 20 μg / mL, and were taken out after immersion at 4°C for 12 hours. They were pre-frozen at -20°C for 24 hours and then freeze-dried to obtain composite nanomaterial 1 loaded with stem cell exosomes, composite nanomaterial 2 loaded with stem cell exosomes, composite nanomaterial 3 loaded with stem cell exosomes, composite nanomaterial 4 loaded with stem cell exosomes, composite nanomaterial 5 loaded with stem cell exosomes, composite nanomaterial 6 loaded with stem cell exosomes, and composite nanomaterial 7 loaded with stem cell exosomes corresponding to Examples 1 to 6 and Comparative Example 1.

[0113] Test Case

[0114] The data of the following test items were analyzed using SPSS17.0 software, and the results of each group were expressed as mean ± standard deviation (x ± s). The results were compared using independent sample t test or one-way analysis of variance. P < 0.05 was considered to be statistically significant, and P < 0.01 was considered to be statistically significant.

[0115] (1) SEM observation of the stent surface

[0116] The cylindrical composite nanomaterial 1 scaffold with a diameter of 5 mm and a length of 1 cm was immersed in a PBS solution of 20 μg / mL stem cell exosomes as the experimental group, and the composite nanomaterial 1 scaffold was immersed in pure PBS as the control group. After being immersed at 4°C for 12 hours, it was taken out and pre-frozen at -20°C for 24 hours before freeze-drying. After gold spraying, the surface was observed using a scanning electron microscope (SEM) with an accelerating voltage of 10 kV.

[0117] Transmission electron microscopy can be used to observe the morphology of human umbilical cord blood mesenchymal stem cell exosomes (HUCB-MCSs-Exo), which are round or oval (such as Figure 1 As shown). The cell uptake experiment showed that human umbilical cord blood mesenchymal stem cell exosomes (HUCB-MCSs-Exo) could be taken up by BMSCs, and human umbilical cord blood mesenchymal stem cell exosomes (HUCB-MCSs-Exo) could be marked by CD9, confirming that the exosomes extracted in Example 1 were human umbilical cord blood mesenchymal stem cell exosomes (HUCB-MCSs-Exo).

[0118] The SEM image of the scaffold of the composite nanomaterial 1 loaded with stem cell exosomes is shown in Figure 5 As shown in the figure, it can be seen that the scaffold is a three-dimensional porous structure with pore sizes ranging from 100μm to 200μm. The pores form a connected structure, the inner wall of the pores is rough, and deposited nanohydroxyapatite particles and scattered human umbilical cord blood mesenchymal stem cell exosomes can be seen.

[0119] The morphology of the human umbilical cord blood mesenchymal stem cell exosomes extracted in Example 1 of the present invention is round or oval, which is basically consistent with the exosome morphology in the existing research. In addition, the cell uptake results show that the extracted human umbilical cord blood mesenchymal stem cell exosome vesicles can be marked by the exosome marker CD9. The above results show that the present invention has successfully extracted exosomes from human umbilical cord blood mesenchymal stem cells (HUCB-MCSs).

[0120] (2) Biocompatibility testing

[0121] P3 generation BMSCs were inoculated into 96-well plates, and the culture medium was aspirated according to the conventional method. 100 μL of the scaffold DMEM extract of composite nanomaterial 1 was added to each well of the experimental group. The extract was prepared by soaking the scaffold of composite nanomaterial 1 loaded with stem cell exosomes in 2 mL DMEM culture medium and then placing it in an incubator at 37°C for 24 hours; the culture medium was replaced in the blank group after 24 hours. The absorbance at a wavelength of 570 nm was detected on an ELISA reader according to the instructions of the MTT kit. The test results are shown in Table 2.

[0122] Table 2

[0123]

[0124]

[0125] The cells were cultured in the leaching medium of the composite nanomaterial 1 scaffold loaded with stem cell exosomes. Compared with the cells cultured in the simple medium, the number of cells did not decrease significantly, indicating that the cells and the composite nanomaterials have good biocompatibility. The present invention found that compared with the control group without adding exosomes, the human umbilical cord blood mesenchymal stem cell exosomes (HUCB-MCSs-Exo) loaded with human umbilical cord blood mesenchymal stem cell exosomes had a more significant effect on the activity of the osteogenic marker alkaline phosphatase and the formation of mineralized nodules.

[0126] The cytotoxicity of the composite nanomaterial 1 scaffold was detected by MTT method. The test results are as follows Figure 6 As shown, at the same detection time point, there was no difference in absorbance value between the scaffold experimental group of composite nanomaterial 1 loaded with stem cell exosomes and the blank group of composite nanomaterial 1 (P>0.05), which shows that the composite nanomaterial 1 scaffold has no significant effect on the proliferation of BMSCs.

[0127] (3) Protein release detection

[0128] 100 μL of PBS was slowly dripped onto the scaffolds of 100 μg of composite nanomaterials 1-7 loaded with stem cell exosomes, and after freeze-drying, placed in an EP tube containing 2 mL of PBS and kept at a constant temperature of 37°C. Samples were taken for protein quantitative detection at 6 h, 12 h, 24 h, 48 h, and 72 h, respectively. The same protein quantitative detection method was used to determine the protein release in the composite nanomaterials loaded with stem cell exosomes corresponding to the composite nanomaterials prepared in Examples 1 to 6 and Comparative Example 1. The test results are shown in Table 3.

[0129] Table 3

[0130]

[0131]

[0132] (4) Osteogenic activity detection

[0133] Take a normal cell culture 6-well plate and divide it into a negative group, a positive group and an experimental group. In the negative group, a 2 mm layer of composite nanomaterial 1 without stem cell exosomes was laid on the bottom of the normal culture plate, and 2*10 4 BMSCs cells were added with 2 mL of DMEM medium to each well; for the positive group, a 2 mm layer of composite nanomaterial 1 without stem cell exosomes was laid on the bottom of the normal culture plate, and 2*10 4 BMSCs cells were added with 2 mL of osteogenic induction medium to each well; in the experimental group, a 2 mm layer of composite nanomaterial 1 loaded with stem cell exosomes was laid on the bottom of the normal culture plate, and then 2*10 4 For BMSCs cells, 2 mL of osteogenic induction medium was added to each well; the medium was replaced every other day, and alkaline phosphatase staining was performed after 14 consecutive days of culture, and Alizarin red staining was performed after 21 consecutive days of culture.

[0134] The results are as follows Figure 7 As shown, in the alkaline phosphatase staining and Alizarin red staining experiments, the addition of exosomes showed higher osteogenic activity compared with ordinary DMEM medium (negative group) and osteogenic induction medium (positive group).

[0135] The composite nanomaterial containing chitosan and nano-hydroxyapatite provided by the present invention is a porous nanomaterial, and the distribution of the pore size of the composite nanomaterial is controlled within a specific range, so that it can load stem cell exosomes while controlling the release of stem cell exosomes at the site of action, so that the exosomes at the site of action quickly reach an effective concentration without making the exosome concentration at the site of action too high. It can also protect the effective load inside the exosomes from being degraded by the body environment.

[0136] Both chitosan and nano-hydroxyapatite have good biocompatibility, which helps to improve the stability of drugs and reduce immunogenicity. At the same time, chitosan and nano-hydroxyapatite materials are easy to process, exist naturally and have relatively low costs, making them economical and feasible in production.

[0137] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A composite nanomaterial, characterized in that: The composite nanomaterial contains chitosan and nano-hydroxyapatite and has a porous structure. In a unit volume of the nanomaterial, the number of pores with a pore size of 50-100 μm accounts for 15-25%, the number of pores with a pore size of 100-150 μm accounts for 35-50%, the number of pores with a pore size of 150-200 μm accounts for 5-18%, and the number of pores with a pore size of more than 200 μm accounts for 10-23%.

2. The composite nanomaterial according to claim 1, characterized in that: In a unit volume of nanomaterials, the number of pores with a pore size of 50-100 μm accounts for 20-25%, the number of pores with a pore size of 100-150 μm accounts for 40-50%, the number of pores with a pore size of 150-200 μm accounts for 10-18%, and the number of pores with a pore size of more than 200 μm accounts for 15-23%; Preferably, in the composite nanomaterial, the average pore diameter is 126-160 μm.

3. The composite nanomaterial according to claim 1 or 2, characterized in that: In the composite nanomaterial, the weight ratio of chitosan to nano-hydroxyapatite is 1:0.05-2, preferably 1:0.1-0.

2.

4. A method for preparing a composite nanomaterial, characterized in that: include: Under acidic conditions, nano-hydroxyapatite and chitosan are mixed and treated to obtain a composite nano-material; the composite nano-material is a porous nano-material, and in a unit volume of the nano-material, the number of pores with a pore size of 50-100 μm accounts for 15-25%, the number of pores with a pore size of 100-150 μm accounts for 35-50%, the number of pores with a pore size of 150-200 μm accounts for 5-18%, and the number of pores with a pore size of more than 200 μm accounts for 10-23%.

5. The preparation method according to claim 4, characterized in that: The acid providing the acidic condition is selected from at least one of acetic acid, lactic acid, citric acid, formic acid and malic acid; Preferably, the acid providing the acidic condition is acetic acid; Preferably, in the acidic condition, the molar concentration of the acid providing the acidic condition is 0.1-0.3 mol / L; Preferably, in the composite nanomaterial, the weight ratio of chitosan to nano-hydroxyapatite is 1:0.05-2, preferably 1:0.1-0.2; Preferably, relative to 1 g of the nano-hydroxyapatite, the amount of the acid used is 250-500 mL.

6. The preparation method according to claim 4, characterized in that: The mixing process also includes adding a cross-linking agent; Preferably, the mass ratio of the cross-linking agent to the chitosan is 5-6:1; Preferably, the cross-linking agent is a glutaraldehyde solution, and the concentration of glutaraldehyde in the glutaraldehyde solution is 25-50 wt %.

7. Use of the composite nanomaterial according to any one of claims 1 to 3 or the composite nanomaterial prepared by the preparation method according to any one of claims 4 to 6 in loading stem cell exosomes, preferably human umbilical cord blood mesenchymal stem cell exosomes.

8. A composite bio-nanomaterial, characterized in that: Comprising a composite nanomaterial and stem cell exosomes loaded on the composite nanomaterial; the composite nanomaterial is the composite nanomaterial according to any one of claims 1 to 3 or the composite nanomaterial prepared by the preparation method according to any one of claims 4 to 6; Preferably, the loading amount of the stem cell exosomes in the unit mass of the composite bio-nanomaterial is 0.1-0.2%.

9. A method for preparing a composite bio-nanomaterial, characterized in that: include: Mixing stem cell exosomes and a composite nanomaterial in the presence of a solvent; the composite nanomaterial is the composite nanomaterial according to any one of claims 1 to 3 or the composite nanomaterial prepared by the preparation method according to any one of claims 4 to 6; Preferably, the mixing conditions include: temperature of 0-4°C, time of 10-14h, pH of 7.2-7.4; Preferably, the concentration of the stem cell exosomes in the solvent is 10-30 μg / mL.

10. Use of the composite bio-nanomaterial according to claim 8 or the composite bio-nanomaterial prepared by the preparation method according to claim 9 as a bone tissue engineering biomaterial.

Citation Information

Cited By

  • Preparation method and application of low-oxygen pretreated pilose antler stem cell exosome preparation

    CN121046306A